2021
DOI: 10.1002/ecy.3309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mangrove cover on coastal erosion during a hurricane in Texas, USA

Abstract: We tested the hypothesis that mangroves provide better coastal protection than salt marsh vegetation using 10 1,008-m 2 plots in which we manipulated mangrove cover from 0 to 100%. Hurricane Harvey passed over the plots in 2017. Data from erosion stakes indicated up to 26 cm of vertical and 970 cm of horizontal erosion over 70 months in the plot with 0% mangrove cover, but relatively little erosion in other plots. The hurricane did not increase erosion, and erosion decreased after the hurricane passed. Data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 37 publications
2
32
0
2
Order By: Relevance
“…However, in our study, mangrove cells inhibited surface sediment accretion post-hurricane. Results from other studies in these same wetlands found that mangrove cover enhanced shoreline retention by reducing vertical and fringe erosion, which is likely attributed to greater soil strength in mangrove cells (Armitage et al 2020, Pennings et al 2021. Coastal vegetation species differentially modify soil strength through organic detritus input, and greater root biomass and organic content in these mangrove cells (Charles et al 2020), and may lower soil bulk density and increase sediment stability (Feagin et al 2009).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…However, in our study, mangrove cells inhibited surface sediment accretion post-hurricane. Results from other studies in these same wetlands found that mangrove cover enhanced shoreline retention by reducing vertical and fringe erosion, which is likely attributed to greater soil strength in mangrove cells (Armitage et al 2020, Pennings et al 2021. Coastal vegetation species differentially modify soil strength through organic detritus input, and greater root biomass and organic content in these mangrove cells (Charles et al 2020), and may lower soil bulk density and increase sediment stability (Feagin et al 2009).…”
Section: Discussionmentioning
confidence: 87%
“…Coastal vegetation species differentially modify soil strength through organic detritus input, and greater root biomass and organic content in these mangrove cells (Charles et al 2020), and may lower soil bulk density and increase sediment stability (Feagin et al 2009). Our research suggests that mangroves function as critical biophysical filters on multiple spatial scales despite storm-driven changes in sediment biogeochemistry, retaining accreted sediments along coastal fringe margins (Charles et al 2020) and reducing sediment even at low plot-scale mangrove cover (Pennings et al 2021). Increases in mangrove cover in coastal wetlands may therefore enhance physical shoreline retention and reduce storm sediment and wrack deposition (Armitage et al 2020, Pennings et al 2021.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations